Assertiveness : how can I say what I mean? - Havelin, Kate, 1961- (Mankato, Minnesota : LifeMatters, 2000)
Defines assertiveness, discusses its value, and offers strategies for readers to improve their assertiveness skills
Includes bibliographical references and index
Keywords: Assertiveness in adolescence; Assertiveness (Psychology)